Analisis Terhadap Hubungan Antara Perusahaan Induk Dengan Anak Perusahaan (Studi PT. Perkebunan Nusantara IV (Persero) dengan PT. Pamina Adolina) - Sofwan Tambunan; Syafruddin Kalo; Sunarmi Sumanrmi (Jurnal Pencerah Bangsa, 2023)
The regulation of legal relations between the holding company and its subsidiaries in limited liability company law in Indonesia still uses the principle of a single company, but in reality the economic activities carried out by the subsidiary and the holding company are synergistic activities. This research discusses legal issues between the holding company and its subsidiaries, namely how is the legal construction of group company arrangements in Indonesia, what are the responsibilities of the holding company as the majority shareholder in a subsidiary company, what are the responsibilities of PTPN IV (Persero) as the holding company of the majority shareholder in PT . Pamina Adolina as a subsidiary.This is a normative juridical research that is descriptive analytical. Sources of data come from primary, secondary and tertiary data collected by library research. Analysis of the data is carried out using a qualitative analysis with a deductive approach. The research results explain that the legal construction of group company arrangements in Indonesia based on Law No. 40 of 2007 still maintains juridical recognition of the legal entity status of the holding company and its subsidiaries as independent legal subjects, even though there is a link between holding company and its subsidiaries. Based on this approach, the regulatory framework for group companies in Indonesia uses a single company approach